2020
DOI: 10.1111/tbed.13646
|View full text |Cite
|
Sign up to set email alerts
|

Application of phage therapy: Synergistic effect of phage EcSw (ΦEcSw) and antibiotic combination towards antibiotic‐resistant Escherichia coli

Abstract: Escherichia coli that are commonly residing in human colon and the strains that cause infections in the gut are called enterohaemorrhagic E. coli (EHEC). Shiga toxin-producing E. coli (STEC), E. coli O157:H7 and E. coli O25:H4 are major human pathogens known to be responsible for infections worldwide (Farfan & Torres, 2012). Moreover, seven E. coli serotypes such as O26, O45, O103, O111, O121, O145 and O157 have been reported as food poisonous bacteria (Singh et al., 2015). Since the introduction of antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…As antibiotic resistant bacteria are becoming more prevalent, new strategies are needed to combat these bacterial infections. Recent experiments show that antibiotics and phages may synergistically target bacterial populations when used in tandem [4,5]. While some studies have revealed that two phage types can synergistically fight bacterial infections [4], we demonstrate that certain virus types that are naturally present in human hosts may inhibit bacterial infection control with antibiotics.…”
Section: Introductionmentioning
confidence: 61%
“…As antibiotic resistant bacteria are becoming more prevalent, new strategies are needed to combat these bacterial infections. Recent experiments show that antibiotics and phages may synergistically target bacterial populations when used in tandem [4,5]. While some studies have revealed that two phage types can synergistically fight bacterial infections [4], we demonstrate that certain virus types that are naturally present in human hosts may inhibit bacterial infection control with antibiotics.…”
Section: Introductionmentioning
confidence: 61%
“…The same occurs in colistin + U1G group, nevertheless, the bacteria during the attempt to develop phage resistance might partially lose resistance to colistin and hence the combination can achieve enhanced killing than when individually treated. Zebrafish model has been used to study the efficiency of bacteriophages in curtailing infections caused by P. aeruginosa, K. pneumoniae, E. coli and E. faecalis [39,[47][48][49]. Nevertheless, majority of studies has compared the effect of antibiotics and phage therapy and scarce reports are available that has studied the combination of antibiotic and phage therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the bacteria during its attempt to develop phage resistance might partially lose resistance to colistin and hence the combination can achieve enhanced killing than when individually treated. Zebrafish model has been used to study the efficiency of bacteriophages in curtailing infections caused by P. aeruginosa, K. pneumoniae, E. coli and E. faecalis [53,[67][68][69] . Nevertheless, the majority of studies have compared the effect of antibiotics and phage therapy and very few reports have studied the combination of antibiotic and phage therapy.…”
Section: Discussionmentioning
confidence: 99%